Properties and applications of PDMS for biomedical engineering: a review - Miranda, Inês (2021)
Polydimethylsiloxane (PDMS) is an elastomer with excellent optical, electrical and mechanical properties, which makes it well-suitable for several applications such as microfluidic and pho-tonics in several areas. Due to its biocompatible feature, PDMS is widely used for biomedical purposes. This widespread led also to the massification of the soft-lithography technique, intro-duced for facilitating the rapid prototyping of micro and nanostructures using elastomeric ma-terials, most notably PDMS. This technique allowed advances on microfluidic, electronic and biomedical fields. In this review an overview of the PDMS properties and some of its commonly used treatments, aiming the suitability to those fields’ needs, are presented. Applications such as microchips in biomedical field, replication of cardiovascular flow and medical implants are also reviewed.